Correlation between extended pelvic lymph node dissection and urinary incontinence at early phase after robot‐assisted radical prostatectomy. (7th December 2022) - Lee, Ken; Shiota, Masaki; Takamatsu, Dai; Ushijima, Miho; Blas, Leandro; Okabe, Ayami; Kajioka, Shunichi; Goto, Shunsuke; Kinoshita, Fumio; Matsumoto, Takashi; Monji, Keisuke; Kashiwagi, Eiji; et al.
Abstract : Objectives: To investigate the impact of extended pelvic lymph node dissection (ePLND) on urinary incontinence (UI) at early post‐surgery robot‐assisted radical prostatectomy (RARP). Methods: Patients who underwent RARP without cavernous nerve sparing were included between 2014 and 2019. Patient data were obtained prospectively. The associations between ePLND and postoperative urinary continence were defined as a maximum of one daily pad use. International prostate symptom score (IPSS) was examined. Expression of synaptophysin and tyrosine hydroxylase (TH) in perilymph node adipose tissue (PLA) was evaluated by immunohistochemistry. Results: In total, 186 and 163 patients underwent RARP with and without ePLND. Urinary continence rate at 1 month postoperatively among patients with ePLND was lower than those without ePLND (24.1% vs. 35.1%, p < 0.05), however, not significantly different at 3, 6, and 12 months after RARP (57.4 vs. 62.6%, 73.1 vs. 74.2%, and 83.0 vs. 81.2%, respectively). Total and voiding plus postvoiding IPSS scores at 1 month were higher in patients with ePLND than in those without ePLND (14.5 ± 0.5 vs. 13.6 ± 0.6, 7.0 ± 0.3 vs. 6.2 ± 0.4, respectively, p < 0.05). In univariate and multivariate analyses, larger prostate volume and ePLND were factors associated with an increased UI rate. Among patients who underwent ePLND, synaptophysin and TH‐positive nerve fibers were detected in PLA. Conclusions: Detection of synaptophysin and TH‐immunopositive nerves suggested denervation of sympathetic and peripheral nerves caused by ePLND might be associated with a higher UI rate and poor urinary symptoms at an early stage after RARP.